Analyzing Students’ Needs for Better Information Literacy In The 21st Century - Siti Luruh Ayu Noerjanah; Sadiah Maulidah (Ilmu Inovasi Nusantara, 2021)
Mastery of information literacy skills has been proven to be important in the era of globalization. Hence the information literacy training is an activity that should be followed by every student. Information literacy skills are also a provision of lifelong learning. The researcher demonstrates the requirements of information literacy in the 21st century. This purpose is to analyze the information literacy in 21st century that the English students should have. This research used a qualitative approach. In addition, this research used a critical literature review as a method for undertaking the data. The researcher presents the information literacy needs in the 21st century. Several criteria were generated to help the researcher to find out the relevant literature and research of information literacy. After conducting the critical literature review of generating the requirements of information literacy in the 21st century, the findings of the research are there are two dimensions (skills and competencies) that should be considered